How should Bank Syariah Indonesia respond to cyber-attacks? Churn, sentiments, and emotions analysis with machine learning - Timur, Yan Putra; Ridlwan, Ahmad Ajib; Fikriyah, Khusnul; Susilowati, Fitriah Dwi; Canggih, Clarashinta; Nurafini, Fira (Universitas Islam Indonesia, 2024)
IntroductionThis study aims to identify the most popular topics and words in Twitter conversations regarding cyber-attacks on Bank Syariah Indonesia that occurred in May 2023. It also seeks to analyze the sentiments, emotions, and potential customer churn of netizens following cyber-attacks.ObjectivesThe objective of this study is to investigate the public's response to cyber-attacks on Bank Syariah Indonesia, focusing on identifying key topics, analyzing sentiments and emotions, and estimating potential customer churn.MethodThis study uses a qualitative method with a sentiment analysis approach utilizing Orange Data Mining software. The data comprises tweets collected from May 10, 2023, to May 24, 2023, using keywords such as “BSI” and “Bank Syariah Indonesia,” resulting in 30,014 tweets. Sentiment and emotion analyses were conducted to categorize tweets and identify the prevalent sentiments and emotions.ResultsThe analysis reveals that the words “BSI,” “Data,” and “Lockbit” are most frequently mentioned, indicating the relevance of the cyber-attackers who targeted Bank Syariah Indonesia. The sentiment analysis showed that 56% of the tweets were neutral and dominated by emotions of joy. The study also identifies a short-term potential churn rate of 1.60% for Bank Syariah Indonesia's total customer base, indicating the risk of customers switching to other banks.ImplicationsThe results highlight the importance of robust cybersecurity measures and quick response strategies for maintaining customer trust and satisfaction. Financial institutions, particularly banks, must prioritize information and technology security to prevent customer churn and ensure the continuity of their services.Originality/NoveltyThis study provides insights into public reactions to cyber-attacks on Islamic banks, emphasizing the role of sentiment and emotion analysis in understanding customer behavior. This offers practical implications for improving risk management and customer retention strategies in the banking sector.